Supervision Strategy of the Indonesian Broadcasting Commission of the Bangka Belitung Islands in Preventing Broadcast Violations of Elections and Regional Head Elections 2024 - Al Kodri, M. Adha; Sari, Patricia Widya; Ashidiq, Abdul Rahman (International Humanity Advance, Business & Sciences, 2025)
The Indonesian Broadcasting Commission of the Bangka Belitung Islands has the authority to supervise broadcasts conducted by broadcasters. The great influence of mass communication shows the importance of broadcasting institutions, including in the implementation of General and Regional Elections. Their presence can provide political knowledge and education to the public. This role is part of mass communication. The magnitude of this role requires supervision of the broadcaster so that it is not used as a tool for political interests that can harm the public. Therefore, this research aims to analyze the supervision strategy carried out by the Indonesian Broadcasting Commission of the Bangka Belitung Islands in preventing broadcast violations in the 2024 General and Regional Elections. The approach used is descriptive qualitative, namely by conducting observations and interviews, up to data presentation, and conclusions. The results show that the supervision strategy carried out in preventing broadcast violations of the General Election and Regional Election in 2024 by conducting coordination meetings with broadcasting institutions, conducting broadcasting behavior guidelines and broadcast program standards schools (involving the community, and students), to the formation of a task force with the General Election Supervisory Agency and the Provincial Election Commission.